Distinctions and blurred boundaries between qualitative approaches and public and patient involvement (PPI) in research. (3rd September 2022) - Mc Menamin, Ruth; Isaksen, Jytte; Manning, Molly; Tierney, Edel
Abstract: Purpose : International health and social care policy increasingly draws on stakeholder experiences and opinions. The distinctions between various approaches to researching "insider" perspectives are contentious. This article explores features (e.g. philosophy, ethics, and power dynamics) of qualitative approaches and public and patient involvement (PPI) in communication disorder research and explicates the blurred boundaries between them. Method : We use two case studies involving PPI contributors with aphasia – an Irish mixed methodologies study and a Danish qualitative study - to illustrate PPI in research and thus demonstrate how researchers can bridge the gap between theoretical considerations and research implementation Result : There are important distinctions between PPI in research and qualitative approaches (e.g. origins, roles, and reimbursement) and many blurred boundaries (e.g. inclusion, openness to mutual learning and "insider" perspectives). A key difference is that PPI contributors take an active role at project level and more flexibility in roles is required in PPI research. These flexible and varied roles reflect the shared decision-making powers between lay and professional researchers. Conclusion : PPI can add innovation to qualitative and mixed methods communication disorder research as illustrated in both case studies. However, researchers wishing to include PPI must embrace and respond to the evolving and flexible nature of PPI relationships and processes. Flexibility, negotiation and continuous reflection on methodological approaches, power dynamics, roles and co-created knowledge will impact and transform the field of research in communication disorders.